2022
DOI: 10.1016/j.ribaf.2021.101573
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 pandemic and economic policy uncertainty: The first test on the hedging and safe haven properties of cryptocurrencies

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(26 citation statements)
references
References 73 publications
0
22
0
4
Order By: Relevance
“…Prior studies have explored how different policy uncertainty affects the cryptocurrency market, for example, economic or political policy (e.g., Colon et al, 2021 , Demir et al, 2018 , Mokni et al, 2022 ; Umar et al, 2021), Chinese economic policy uncertainty (e.g., Chen et al, 2021 , Yen and Cheng, 2021 ), and Twitter-based economic policy uncertainty ( Wu et al, 2021 ).…”
Section: Brief Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior studies have explored how different policy uncertainty affects the cryptocurrency market, for example, economic or political policy (e.g., Colon et al, 2021 , Demir et al, 2018 , Mokni et al, 2022 ; Umar et al, 2021), Chinese economic policy uncertainty (e.g., Chen et al, 2021 , Yen and Cheng, 2021 ), and Twitter-based economic policy uncertainty ( Wu et al, 2021 ).…”
Section: Brief Literature Reviewmentioning
confidence: 99%
“… Jiang et al (2021) investigated the interconnections between economic policy uncertainty and found a negative spillover of economic policy uncertainty and COVID-19 on cryptocurrencies. Recently, Mokni et al (2022) investigated the effect of economic policy uncertainty on five cryptocurrencies before and during COVID-19 and suggested Gold and cryptocurrencies cannot act as a strong hedge against economic policy uncertainty before and during the COVID-19 pandemic. Several other studies also found cryptocurrency market actively reacts to different policy uncertainty ( Colon et al, 2021 ; M. Umar et al, 2021; Wu et al, 2021 ).…”
Section: Brief Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…These assets marked a significant contribution by their speculative nature and their substitutive character of conventional currencies ( Mokni & Ajmi, 2021 ). In another vein, cryptocurrencies are alluring investment tools as they are often considered “safe haven” assets against other asset classes (e.g., Bouri, Gupta, Tiwari, & Roubaud, 2017 ; Urquhart & Zhang, 2019 , among others) or uncertainty ( Mokni, 2021 ; Mokni, Al-Shboul, & Assaf, 2021 ; Mokni, Youssef, & Ajmi, 2022 ; Wu, Tong, Yang, & Derbali, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Second, this paper contributes to studies of COVID-19’s impact on financial markets. Prior literature mainly focuses on the negative impact of COVID-19 on stock markets ( Liu et al, 2020 ; Contessi and De Pace, 2021 ; Mazur et al, 2021 ), and tries to find safe havens against stock markets during the pandemic ( Salisu et al, 2021 ; Yousaf et al, 2021 ; Yousaf and Ali, 2021 ; Mokni et al, 2022 ). However, few studies offer direct empirical evidence on what channels can reduce the negative impact of COVID-19 on financial markets.…”
Section: Introductionmentioning
confidence: 99%